The Validity of Prayer Importance Scale (PIS) - Małgorzata Tatala; Marcin Wojtasiński (Religions, 2021)
Prayer is a central element of religiosity but research has focused primarily on distinguishing its types and analyzing its functional aspect. A particularly important issue is the subjective evaluation of prayer importance, which so far has not been reflected in the form of an independent psychometric tool. This is why the goal of the presented study was to develop Prayer Importance Scale (PIS) based on Tatala’s definition of the concept. Two studies were conducted to verify reliability and validity of the tool. The proposed model was found to fit the data well. Correlations of PIS with basic parameters of religiosity: religious awareness, religious feelings, religious decisions, bond with a fellowship of believers, religious practices, religious morality, religious experience and forms of profession of faith were found to be significant. PIS can be a quick method providing information on the degree of religiosity and be used in participant selection in research studies.